A saúde mental dos trabalhadores em home office e a efetividade da proteção social do trabalhador - Sousa, Lúcia de Fátima Moura Paiva de (2022)
The main objective of this dissertation was to clarify the central theme of the mental health of workers in home office and the effectiveness of social security protection. The theme developed and the path traced deserve concern since with the COVID-19 pandemic, companies have increasingly had to maintain their activities to establish that their employees work in the home office mode, therefore, a better understanding of the subject is necessary, and on the dimension of health within the concept of the fundamental right to decent work, which must be analyzed in view of working conditions and the organization of work in all its forms, in particular, home office work. In order to do so, a bibliographic review was carried out about the Democratic State of Law, as well as its axiological principles. The effectiveness of the Fundamental Rights to decent work and the effectiveness of social security protection were analyzed, with regard to the worker's mental health and also regarding the observance of ergonomics rules. The Study sought to highlight, from a legal point of view, the employer's civil liability, regarding the physical, mental and safety of the worker in home office and its social security consequences, due to the current social moment, where this form of work is in emphasis. For this, it also dedicated itself to the study of the home office, demonstrating the factors that triggered its development, its peculiarities and main characteristics. Based on such bases, the present study sought to build the premises related to illness in home office workers, the employer's civil liability and its consequences in Social Security Law, based on a more current and compiled legislation, which covers situations such as the main accidents resulting from the working from home, the prevention of occupational diseases, in addition to the psychosocial risks at work, alerting to the tolerance of the Brazilian State in relation to these risks and the lack of specific legislation on the prevention and strengthening of social security protection for workers at home office. The structure was partially changed in order to address more social security issues that are precisely the area of law under study, since there is a high incidence of labor law in writing